circSSU72 Promotes Cell Proliferation, Migration and Invasion of Papillary Thyroid Carcinoma Cells by Targeting miR-451a/S1PR2 Axis - Zhang, Zeyu; Xia, Fada; Yao, Lei; Jiang, Bo; Li, Xinying (Frontiers in Cell and Developmental Biology, 2022)
Introduction: Thyroid cancer is the most common endocrine malignancy with Papillary Thyroid Carcinoma (PTC) as the most common pathological type. Due to low mortality but a high incidence, PTC still causes a relatively heavy burden on financial costs, human health, and quality of life. Emerging researches have indicated that circular RNAs (circRNAs) play a significant regulatory role in various cancers, including PTC. However, the functions and mechanisms of circRNAs derived from SSU72 remain unknown. Method: The expression level of circRNAs derived from the exons of SSU72, miR-361-3p, miR-451a, and S1PR2 was evaluated by qRT-PCR assay or western blot assay. The interactions between circSSU72 (hsa_circ_0009294), miR-451a, and S1PR2 were verified by dual-luciferase reporter assay. Effects of circSSU72, miR-451a, and S1PR2 on cell proliferation, migration, and invasion were confirmed by colony formation assay, cell counting kit-8 (CCK-8), wound healing assay, and Transwell assays in vitro. Results: circSSU72 was upregulated in PTC; circSSU72 knockdown inhibited PTC cell proliferation, migration, and invasion. In addition, circSSU72 could negatively regulate miR-451a by functioning as a sponge. circSSU72 promoted PTC cell proliferation, migration, and invasion by targeting miR-451a in vitro. We further found that miR-451a inhibited PTC cell proliferation, migration, and invasion by regulating S1PR2. Overall, the circSSU72/miR-451a/S1PR2 axis might influence PTC cell proliferation, migration, and invasion. Conclusions: Overall, circSSU72 (hsa_circ_0009294)/miR-451a/S1PR2 axis may promote cell proliferation, migration, and invasion in PTC. Thus, circSSU72 may serve as a potential biomarker and therapeutic target for PTC.